Seeing Is Believing(?): Blurred Boundaries and Loving Looks in Nancy Burson’s Art - Kérchy, Anna (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Nancy Burson is a contemporary American digital artist, photographer, bom in 1948. Her work is shown in museums and galleries internationally including major exhibitions at The International Center of Photography and the New Museum in New York City, The Venice Biennale, The Contemporary Arts Museum in Houston, and The Museum of Contemporary Photography in Chicago. She has served as a visiting professor at Harvard and was a member of the adjunct photography faculty at New York University’s Tisch School of the Arts. “Seeing and Believing” was the title of her traveling 2002 retrospective originating at the Grey Art Gallery, and nominated for Best Solo Museum Show of the Year in New York City by the International Association of Art Critics.